POSTURAL BALANCE, MUSCLE STRENGTH, AND RISK OF FALLS IN ELDERLY PEOPLE WITH CHRONIC OSTEOMYARTHRITIC DISEASE (CIPEEX, 2025)
Longevity brings new challenges that demonstrate the importance of healthy aging and the inclusion of older adults in society. However, many older adults find it difficult to maintain their ability to move independently and safely, and thus, restricted mobility can lead to several undesirable consequences, such as an increased risk of falls and loss of independence. Thus, the objective of this study is to investigate the relationship between lower limb muscle strength, postural balance, and the risk of falls in older adults with osteoarticular diseases. This is a cross-sectional, observational, analytical study. The study population consisted of 106 elderly individuals regularly enrolled at UniAPI, of whom only 60 met the inclusion criteria. Sociodemographic information was collected, and assessments were made on the incidence of falls, muscle strength, and static balance. In addition, the sit-to-stand test was used to assess lower limb muscle strength, and the Sway protocol on a force platform was used to assess static balance. The study showed that those without knee osteoarthritis performed more repetitions in the sit-to-stand test than those with osteoarthritis, concluding that the risk of falls in older adults with osteoarthritis is a worrying factor that should be addressed through preventive measures aimed at improving body instability.
Keywords: Elderly; Fall accidents; Postural balance; Osteoarthritis